Learning Islamic Religious Education and Character By Using Audio Visual Media in Elementary Schools - Sukarto, Sukarto; Arum, Maulida (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Learning Islamic religious education and character using audio visual media at school base. This research aims to determine the implementation of learning using audio-visual media in grades 4 and 5. This research was conducted at SDN 6 Sokong, with students in grades 4 and 5 in semester 2. The method used in this research is field research, with a qualitative descriptive approach. The subject of this research is the media audio visuals using LCD, teachers and students. In this research, data collection techniques use interview, observation and documentation techniques, and data analysis techniques in this research use data condensation, data presentation and drawing conclusions. The results of this research show that the implementation of Islamic religious education and character learning uses audio media. visuals in grades 4 and 5 went well, because according to planning learning Which made, and make students enthusiastic, finally the teacher carries out a learning evaluation to find out the extent to which the goals have been achieved learning.